ANALISIS LITERASI DIGITAL SISWA DI MTs PANCASILA KOTA BENGKULU DALAM MENGAKSES SUMBER BELAJAR - Jelita, Dian; Zahra, Karin; Hariyanti, Dewi; Sucilia, Annisa; Adella, Neti (FAKULTAS TARBIYAH UNIVERSITAS QOMARUDDIN GRESIK - JAWA TIMUR, 2025)
Advances in information and communication technology have brought significant changes to the world of education, creating new challenges for students in accessing and evaluating information. Digital literacy is the key to ensuring students are not only able to use technology, but also have the critical ability to sort and understand correct and relevant information. This research aims to analyze the level of digital literacy of students at MTs Pancasila, Bengkulu City and the factors that influence it. The research results show that although most students have basic skills in operating technology, they still have difficulty evaluating information critically and selecting valid and relevant information. Internal factors such as interest in learning and technology experience, as well as external factors such as the role of teachers, parents and technology infrastructure in schools play a role in shaping students' digital literacy levels. This research suggests integrating digital literacy skills in the curriculum and increasing support from teachers and parents to develop students' critical thinking skills in using technology.